A Review on Low-Dimensional Nanomaterials: Nanofabrication, Characterization and Applications - Paras; Kushal Yadav; Prashant Kumar; Dharmasanam Ravi Teja; Sudipto Chakraborty; Monojit Chakraborty; Soumya Sanjeeb Mohapatra; Abanti Sahoo; Mitch M. C. Chou; Chi-Te Liang; Da-Ren Hang (Nanomaterials, 2022)
The development of modern cutting-edge technology relies heavily on the huge success and advancement of nanotechnology, in which nanomaterials and nanostructures provide the indispensable material cornerstone. Owing to their nanoscale dimensions with possible quantum limit, nanomaterials and nanostructures possess a high surface-to-volume ratio, rich surface/interface effects, and distinct physical and chemical properties compared with their bulk counterparts, leading to the remarkably expanded horizons of their applications. Depending on their degree of spatial quantization, low-dimensional nanomaterials are generally categorized into nanoparticles (0D); nanorods, nanowires, and nanobelts (1D); and atomically thin layered materials (2D). This review article provides a comprehensive guide to low-dimensional nanomaterials and nanostructures. It begins with the classification of nanomaterials, followed by an inclusive account of nanofabrication and characterization. Both top-down and bottom-up fabrication approaches are discussed in detail. Next, various significant applications of low-dimensional nanomaterials are discussed, such as photonics, sensors, catalysis, energy storage, diverse coatings, and various bioapplications. This article would serve as a quick and facile guide for scientists and engineers working in the field of nanotechnology and nanomaterials.